Towards Structured Biomedical Content Authoring and Publishing - Mbouadeu, Steve Fonin; Abbas, Asim; Ahmed, Faizan; Keshtkar, Fazel; De Bello, Joan; Bukhari, Syed Ahmad Chan (2022 IEEE 16th International Conference on Semantic Computing (ICSC), 2022)
Significant barriers exist in achieving fast and accurate access to online biomedical content because of the proliferation of unstructured biomedical information. Accompanying semantic annotations with growing biomedical content is critical to enhancing search engines' context-aware indexing, improving search speeds and retrieval accuracy. We have developed "Semantically": a biomedical structured content authoring and publishing framework to enhance biomedical content FAIR-ness (Findability, Accessibility, Interoperability, and Reusability). Finding the appropriate semantic vocabulary to annotate biomed-ical content is time-consuming and technically challenging. "Semantically" automates and streamlines this process for users by recommending highly accurate annotations from an array of biomedical ontologies. Similarly, preserving content-level se-mantics at the content publishing stage to foster semantic search remains a critical research challenge. "Semantically" addresses this obstacle by extending schema.org, a community-agreed and research engine endorsed guideline for publishing structured content on the web. In future works, we aim to improve the biomedical content annotation process through a socio-technical approach by enabling a collaborative annotation scheme. The demo of the system is accessible at: https://gosemantically.com/